Experiment on Making Dessert Boxes through a Combination of Cassava and Yoghurt - Prasetyo, Hendro; Hermawan, Hary (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
This experiment aims to combine cassava and yoghurt into a dessert box, focusing on the health benefits of both ingredients. Cassava supports digestive health, provides energy, prevents diabetes, and protects muscle tissue, while yoghurt is rich in calcium, vitamin D, and protein, promoting bone, dental, and digestive health. The objective of this study is to revive the popularity of cassava, which has become less common in modern diets, by transforming it into a trendy dessert with yoghurt. The study also examines adolescent preferences regarding taste, color, texture, and aroma. The results showed that the combination of cassava and yoghurt offers a unique taste, blending the sourness of yoghurt, the savory flavor from coconut milk, and the sweetness of cassava. The texture is smooth and soft due to the high water content in the steamed cassava, which is then pounded and processed to achieve a creamy consistency, making it an appealing and nutritious dessert option.